Comparison between free and pedicled anterolateral thigh flaps and surgical outcomes in soft tissue reconstruction - Hamid, Agus Roy Rusly Hariantana (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND The anterolateral thigh (ALT) flap, harvested either as a free flap with microsurgical anastomosis or as a pedicled flap with an intact blood supply, is widely used to repair soft tissue defects. This study aimed to evaluate the ALT flap, both free and pedicled variants, as a reliable option for reconstruction, focusing on flap viability and complications. METHODS This cross-sectional study included 30 patients who underwent free or pedicled ALT flap reconstruction at IGNG Ngoerah Hospital, Bali, between 2020 and 2024. Inclusion criteria were complete medical records and confirmed vascular flow on preoperative Doppler ultrasound. Statistical analysis was performed using Fisher’s exact test for bivariate analysis. The primary outcomes evaluated were the incidence of complications and their association with the type of flap. RESULTS ALT flaps were used as free flaps in 60% of cases and as pedicled flaps in 40%. Most patients were adult males, with flap placements mainly in the abdomen (36.7%). Wound dehiscence and necrosis occurred in 13.3% of cases. Wound dehiscence and complications requiring follow-up occurred more frequently in patients undergoing free flap procedures (38.9% versus 8.3%, p<0.001; 22.2% versus 0%, p = 0.001). In contrast, the incidence of necrosis was comparable between the two flaps (16.75% versus 8.3%, p = 0.632). CONCLUSIONS The free ALT flap showed a higher risk of partial flap necrosis and required more intensive monitoring. Pedicled ALT flap demonstrated a lower complication rate and more straightforward postoperative care, suggesting a more favorable option.